Bile acids as potential pheromones in pintado catfish Pseudoplatystoma corruscans (Spix &Agassiz, 1829): eletrophysiological and behavioral studies - Giaquinto, Perclia Cardoso [UNESP]; Barreto, Rodrigo Egydio [UNESP]; Volpato, Gilson Luiz [UNESP]; Fernandes-de-Castilho, Marisa; Goncalves-de-Freitas, Eliane [UNESP] (Soc Brasileira Ictiologia, 2015)
Bile acids are potent olfactory and gustatory stimulants for fish. Electro-olfactogram recording was used to test whether the olfactory epithelium of pintado catfish Pseudoplatystoma corruscans is specifically sensitive to bile acids, some of which have been hypothesized to function as pheromones. Five out of 30 bile acids that had been pre-screened for olfactory activity in fish were selected. Cross-adaptation experiments demonstrated that sensitivity to bile acids is attributable to at least 3 independent classes of olfactory receptor sites. The taurocholic acid (TCA) and taurochenodeoxycholic acid (TCD) were the most potent compounds. By using avoidance/preference tests, we found that Pseudoplatystoma corruscans prefers water containing TCA. Bile acids are discriminated by olfactory epithelium of pintado, supporting that these compounds could function as pheromones.
Keywords: Behavior; Electro-olfactogram (EOG); Olfaction; Preference test